Big data trend: knowledge discovery on the unstructured data - Abu Muntalib, Shamsiah; Sidi, Fatimah; A. Jabar, Marzanah; Ishak, Iskandar (2014)
Knowledge may be discovered from various sources of information. Knowledge Discovery in Database (KDD) is the process of discovering valuable knowledge from data collection. Data warehousing and traditional data processing and analysis of structured data via Relational Database Management System (RDBMS) is accessibility towards standard IT technologies and unsatisfied the challenges of big data. The current biggest challenge is a matter of turning big data into Knowledge Discovery insight that enable organizations to facilitate effective decision making. The purpose of this paper is to explore the knowledge discovery and the challenges in big data real-time setting. A technique of knowledge discovery in real-time insight will be proposed in order to extract valuable knowledge.